Patients' Perspectives and Advice on How to Discuss Sexual Orientation, Gender Identity, and Sexual Health in Oncology Clinics. (December 2020) - Cathcart-Rake, Elizabeth; O'Connor, Jennifer; Ridgeway, Jennifer L.; Breitkopf, Carmen Radecki; Kaur, Judith S.; Mitchell, Jessica; Leventakos, Konstantinos; Jatoi, Aminah
Objective: This study sought to understand the patients' perspective of what contributes to an absence of discussions of sexual orientation (SO), gender identity (GI), and sexual health in cancer care. Methods: Patients were recruited from oncology, gynecology, and a gender transition clinic to participate in semistructured interviews, which were analyzed with qualitative methods. Results: A total of 25 patients were interviewed, shedding light on 2 themes. The first was that these conversations are important but infrequent. One patient explained, "…. we know people who have had sex changes…[they] would have appreciated that question." In response to whether sexual health was ever brought up, one patient responded, "No doctor ever has." Patients described unaddressed issues: "There have been times, you know, we've wondered if it was okay to make love." The second theme consisted of 4 pragmatic, patient-provided points to facilitate discussions: (1) implementation of a scale of 1 to 10 (with 10 being comfortable) to first gauge patients' comfort in talking about SO, GI, and sexual health; (2) having the health-care provider explore the topic again over-time; (3) making sure the health-care provider is comfortable, as such comfort appears to enhance the patient's comfort ("I have a doctor here, a female doctor, who just matter of fact will ask if I get erections and so on because of the medication she's giving me);" and (4) eliminating euphemisms (one patient stated, "I don't know what you mean by 'sexual health'."). Conclusion: Oncology health-care providers have a unique opportunity and responsibility to address SO, GI, and sexual health.